Kesulitan Mahasiswa dalam Menerjemahkan Teks Bahasa Inggris (Studi kasus di Sekolah Tinggi Ilmu Tarbiyah Makrifatul Ilmi Bengkulu Selatan) - Yogi Irawan (Indonesian Journal of Social Science Education (IJSSE), 2022)
This study aims to describe the recognition of student difficulties and their causes in translating English texts into Indonesian by students of STIT Makrifatul Ilmi South Bengkulu Study Year 2022/2023. The population of this study were students with a sample of 50 students. The instruments of this research are questionnaires and interviews. the data were analyzed using the percentage formula. The results showed that the factors that caused students of STIT Makrifatul Ilmi South Bengkulu Academic Year 2022/2023 to experience difficulties in translating English texts into Indonesian, are: 1. On linguistic factors or Linguistics, most of the students' knowledge and understanding of finding words not listed in the dictionary (26.87%) in translation is still limited, due to the lack of open dictionaries, and 2. Non-linguistic factors, most of the students' knowledge and understanding in translating texts related to medical (40.30%), technical (37.31%), chemistry (34.33%) are still poorly understood, due to the lack of scientific dictionaries.